Class Directors and Parents: Contrasting Principles and Practices - Sarmento, Teresa; Martins, Fernanda; Gomes, Carlos; Antunes, Fatima (International Journal about Parents in Education, 2023)
The relevance of the relationship between schools and families to foster educational success, and as a principle of the implementation of democratic practices, enhancing the promotion of equality, is, nowadays, more accepted, even though the building of this collaboration falls short of all speeches and intentions. The class director’s (CD) position provides a space in which this relationship can be solidified with the mediating role assigned to the CD being just one aspect of the triple function that characterizes that post. In this article, empirically based on a qualitative study, made up of interviews to CDs, we seek to analyze the latter’s representations on the participation of parents/guardians (PG) in the educational practices in schools. From their narratives, we propose an interpretation and a discussion that seek to discuss the relational complexity between the CDs and the Parents, which has as its origin the heterogeneity of their cultures, namely the social cleavage in the participation of families, and, also, the kind and levels of participation that are offered to or claimed by parents in the sessions organized by the CD.